Syzygium sirindhorniae (Myrtaceae), a new species from Thailand - Chantaranothai, Pranom; Suksathan, Piyakaset; Wongnak, Methee (Phytotaxa, 2016)
A new species, Syzygium sirindhorniae, from Thailand, is described, illustrated and compared with Syzygium bokoense. This species is known from a restricted locality in northern Thailand which is within a protected area. A conservation status of Near Threatened (NT) is merited.